PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN KEAKTIFAN SISWA - Isnaeni, Muflihatul; Hasibuan, Akmal Rizki Gunawan; Ghofur, Abdul (Al-Ihsan: Journal of Community Development in Islamic Studies, 2024)
The aim of this service is to make the children of TPA Nurul Karomah Ridogalih more active and understand Islamic religious lessons, especially the sirah nabawiyah of Muhammad SAW. namely the last Prophet of Islam. The research method was carried out in three stages, namely the first stageconducting surveys and observations regarding place and time, carrying out permits and interviews with the TPA administrators as well as making powerpoints and preparing Islamic films about sirah nabawiyah Muhammad SAW, then the next stagecarry out planned activities in the form of showing Islamic films togetherand the final stageprovide conclusions, appreciation and document activities that have been carried out as a form of report on activities. The result of this community service is that children become more enthusiastic, active and understand the latest learning media (interactive). Where this is also an idea for teachers when teaching ngaji so that TPA Nurul Karomah Ridogalih children do not get bored in learning. So there needs to be special attention from the government regarding learning facilities and infrastructure, in order to support teaching and learning activities for children and teachers